Towards a coupled model to investigate wave–sea ice interactions in the Arctic marginal ice zone - Boutin, Guillaume; Lique, Camille; Ardhuin, Fabrice; rousset, clement; Talandier, Claude; Accensi, Mickaël; Girard-Ardhuin, Fanny (The Cryosphere, 2020)
International audience The Arctic marginal ice zone (MIZ), where strong interactions between sea ice, ocean and atmosphere take place, is expanding as the result of ongoing sea ice retreat. Yet, state-of-the-art models exhibit significant biases in their representation of the complex ocean-sea ice interactions taking place in the MIZ. Here, we present the development of a new coupled sea ice-ocean wave model. This setup allows us to investigate some of the key processes at play in the MIZ. In particular, our coupling enables us to account for the wave radiation stress resulting from the wave attenuation by sea ice and the sea ice lateral melt resulting from the wave-induced sea ice fragmentation. We find that, locally in the MIZ, the ocean surface waves can affect the sea ice drift and melt, resulting in significant changes in sea ice concentration and thickness as well as sea surface temperature and salin-ity. Our results highlight the need to include wave-sea ice processes in models used to forecast sea ice conditions on short timescales. Our results also suggest that the coupling between waves and sea ice would ultimately need to be investigated in a more complex system, allowing for interactions with the ocean and the atmosphere.